Cóż po pedagogice w ponowoczesności? - Śliwerski, Bogusław (Annales. Etyka w Życiu Gospodarczym, 2012)
This article depicts five approaches to pedagogy, which can be recognized in the course of history: 1) Pedagogy as a philosophy (science of man, paideia, educational anthropology), 2) pedagogy as an independent discipline of humanities, 3) pedagogy as a subject of academic and vocational studies, 4) pedagogy as a subjective theory of education and 5) pedagogy as a community intellectual formation. I am still looking for answers to the question, which of these approaches raises criticism or points to the evolution of educational sciences and schooling as a helpful reflection for practitioners and new directions in researches.